Pemberdayaan Mahasiswa Penerima Beasiswa Lazismu UNISA Bandung Melalui Kewirausahaan Sosial - Minhajuddin Minhajuddin; Nurul Aziz Pratiwi; Dhenahi Jerfiani Wendiyana (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Lack of access to higher education due to economic conditions remains a problem in West Java, making it necessary to implement sustainable empowerment efforts for scholarship recipients. This community service initiative aims to develop social entrepreneurship as a strategy to empower students receiving the Lazismu Scholarship at the UNISA Bandung Campus while simultaneously supporting the institution’s fundraising efforts. The methods employed include seminars, workshops, and participatory mentoring for 16 students, with a focus on designing social projects and developing digital-based fundraising. The results of the activity demonstrated an increase in understanding and social entrepreneurship skills, the development of sustainable social project designs, and heightened student awareness of their role in social fundraising. This program has implications for strengthening the role of students as agents of empowerment and supports the sustainability of educational philanthropy programs.